MENINGKATKAN KOMPETENSI GURU SEKOLAH BINAAN DALAM MENYUSUN RPP MELALUI SUPERVISI AKADEMIK BERKELANJUTAN DI SDN 009 BANGUN PURBA KABUPATEN ROKAN HULU - Syaharuddin Siregar (JURNAL PENDIDIKAN ROKANIA, 2019)
This study aims to see the extent of the principal's academic supervision steps so as to improve teacher competency in the preparation of the Learning Implementation Plan (RPP). The results obtained from this study, academic supervision on an ongoing basis is scientifically proven to be able to improve the competence of teachers in preparing RPP in SD Negeri 009 Bangun Purba. This is proven by the increasing number of teachers who make lesson plans. Likewise, the good quality increased from the average cycle I meeting amounted to 75%, cycle I meeting 2 amounted to 87.5%, cycle II meeting 1 amounted to 100% and cycle II meeting 2 amounted to 100% after academic supervision. In addition, teacher competence in developing lesson plans has increased to 100%.